Fluoroquinolone-Resistant Escherichia coli: Mechanisms of Resistance, Environmental Factors Influencing Resistance and Clinical Implications - Bilel Hassen; Ahlem Jouini (Infectious Microbes & Diseases)
Abstract. Fluoroquinolones are critical antibiotics for treating bacterial infections, especially those caused by Escherichia coli in human or veterinary medicine. However, increasing resistance to these antibiotics has become a serious public health issue, impacting clinical outcomes and treatment efficacy. Understanding the mechanisms driving fluoroquinolone resistance in E. coli and the environmental factors influencing the spread of resistance is essential for developing effective strategies to combat this issue. Fluoroquinolone resistance in E. coli is driven primarily by target site mutations, the activation of efflux pumps, reduced cell permeability and the acquisition of plasmid-mediated resistance genes. These mechanisms collectively increase the ability of E. coli to survive antibiotic exposure. Moreover, environmental stressors such as heavy metals play a significant role in sustaining and disseminating resistance genes. The presence of plasmid-borne resistance elements further facilitates horizontal gene transfer between bacterial populations, complicating infection control efforts. Given the complexity and multifactorial nature of fluoroquinolone resistance, an integrated approach is urgently needed. This includes reinforcing antibiotic use stewardship, implementing stricter environmental controls and enhancing surveillance across clinical and environmental settings. Coordinated efforts in these areas are critical to preserving the effectiveness of fluoroquinolones and safeguarding public health.